GAMBARAN PASIEN GERIATRI MELAKUKAN SWAMEDIKASI DI KABUPATEN SLEMAN - Supadmi, Woro (Universitas Ahmad Dahlan, 2013)
The increase in life expectancy caused geriatric population is also increasing. Geriatric patient is identicalto the decline in physiological function that can lead to various diseases. Self medication in geriatric requirespecial attention from the pharmacist. The purpose of this study was to determine the description of geriatric thatdoes self medication and assosation factors in geriatric patients doing the self medication in Sleman. This researchwas conducted using a survey to determine the presence of pharmacy in Sleman. Determination of pharmaciesconducted with a purposive sampling technique and determination of areas of research subjects or respondentswith accidental sampling. Subjects were geriatric patients with age> 60 years who did self medication inpharmacies. The data were analyzed by using chi-square statistic to determine which are the most influentialassociation factors. The research subjects in this study was 38 respondents. The pattern of disease that occur ingeriatric patients who performs a self-medication is a chronic 12 respondens, non-respondens and 16 non chronicrespondens ten respondens is unknown. Factors that association geriatric patients that is doing self medication isown of health insurance. The results of the chi square test showed that the sex factor with OR 1,11 ( p >0,05),ownership asurance (OR = 1,841,p < 0,05,CI : 1,184 â 2,184) is a factor of self association with geriatric patientsmedications at the pharmacy of district Sleman.